Parâmetros métricos da traqueia e suas correlações com o perímetro torácico, peso e comprimento corporal de cães (Canis familiaris, linnaeus, 1758) sem raça definida - Guimarães, Gregório Corrêa; Polegato, Bárbara Roberta Lorenzato; Rosa, Matheus Camargos de Britto; Guimarães, Camila Souza de Oliveira; Nascimento, Liliane Rangel; Santos, André Luiz Quagliatto; Machado, Márcia Rita Fernandes [UNESP]; Oliveira, Fabrício de Singaretti (My University, 2012)
The present study aimed to analyze metric data from the trachea of dogs and to correlate them with the thoracic girth, body length and weight. We used 48 dogs of unknown breed, 19 males and 29 females. The animals were weighed and then body length, thoracic girth, length and diameter of the trachea, and the number of tracheal rings were measured. The weight of dogs ranged from 4.2 to 21.5 kg, body length from 40.6 to 81.0 cm and thoracic girth from 36.0 to 63.5 cm. The trachea exhibited a total number of tracheal rings between 32 and 43, length between 13.0 and 23.4 cm, diameter of the cervical portion between 11.0 and 23.5 mm and in the thoracic portion between 8.2 and 20.9 mm. We also evaluated the tracheal termination skeletopy, which maintained relations with the 2nd (2.0%), 3 (6.3%), 4 (20.8%) or 5 (12.5%) intercostal spaces, and with the 3rd (6.3%), 4th (35.4%) or 5th (16.7%) ribs. Strong positive correlations of tracheal length with body weight (rS = 0.756, p <0.001), body length (r = 0.808, p <0.001) and thoracic girth (r = 0.735, p <0.001) were found. Therefore, the anatomical study of the trachea provides morphological subsidies for the realization of clinical and surgical procedures in this organ, being an important tool in veterinary practice.
Metric parameters of the trachea and their correlations with thoracic perimeter, weight and body length of unknown breed dogs (Canis familiaris, linnaeus, 1758)
Keywords: Body correlation; Dogs; Tracheal biometrics